كفاءة قراءة الفهم للنص العربي لتلاميذ الفصل العاشر المدرسة الخيرية العالية الإسلامية بسيمارانج عند نظرة تصنيف باريت "TAKSONOMI BARRET" - Siti Khurotun Ayuni; Muhammad Rasyid Ridha (AL LUGHAH, 2022)
This study aims to determine the reading ability and understanding Arabic texts in Class X MA Al-Khoiriyyah Semarang according to Barrett's taxonomy. This study reveals students' reading ability Arabic texts comprehension according to Barrett's taxonomy theory. The type of research used in this research is quantitative research, and the research method used in this study is descriptive quantitative research using observational methods. And data collection in in this study use a test (multiple choice test).The result of this research is the average percentage of students' reading comprehension ability of Class X MA Al-Khoiriyyah Semarang is 46% with almost medium category. The number of students with reading comprehension skills with a perfect score is 1 person or 3%, with a good score there is 1 person or 3%, with an adequate score there are 9 people or 30%, with a moderate score there are 3 people or 10%, with an almost average score there is 1 person or 3%, with a low score there are 2 people or 7%, with a very low score there are 3 people or 10%, with a bad score there are 6 people or 20%, with a very bad score there are 4 people or 13%.الكلمات المحورية: Reading; comprehension; Barret’s taxonomy;